Sustainable agri-pricing towards smallholder's profit: A modified buffer stock operations model under B2B contractual supply chain. (October 2022) - De, Arkajyoti; Prakash Singh, Surya
Highlights: Inefficient agri-subsidy policy lowers smallholder farmers' and retailers' profits. Traditional BSO policy leads to high market distortion and low social welfare. This study modifies the BSO model to propose an efficient price support policy. Proposed model provides higher price to drivers compared to traditional BSO model. Study analyzes the effect of cooperativeness in supply chain channel leadership. Abstract: Random growing demand for high-quality agri-products raises a pseudo pressure on mass-producing Asian tropical regions and lowers Asian smallholders' profit. Literature indicates that the Buffer stock operations (BSO) policy performs well in maintaining sustainable profit for smallholder farmers and retailers. However, with the changing market and growing demand, the conventional BSO lacks efficiency in policymaking and incorporates market distortion. The outburst of COVID-19, random market intervention, growing e-commerce portals, and increasing price declination in the physical market have significantly reduced the smallholders' profit. Thus, this paper modifies the conventional model and proposes a B2B contractual supply chain framework to integrate the BSO model. The supply chain framework considers two different channel leadership strategies, Government Leadership and Farmer Leadership. Following the leadership strategies, this study is concerned with the equilibrium state of the supply chain drivers (the farmer, the retailer, and the government). The proposed framework formulates the model through Stackelberg game modeling and solves using sub-game perfect Nash equilibrium. The theoretical results (Lemmas) ensure that the government leadership strategy facilitates an equilibrium state and sets an optimal profit for farmers and retailers and an optimal social welfare function. Although the farmer's leadership strategy ensures an equilibrium state between the farmer and the retailer, it neither guarantees an equilibrium and optimal state between farmers and government nor an optimal social welfare function. The numerical case illustration considers a wide variety of the market's price sensitivity coefficients. It guides the policy-maker and the supply chain drivers to understand strategy selection better.